2004
DOI: 10.1080/02827580410019436
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of laser-derived tree height estimates by means of photogrammetric techniques

Abstract: Calibration of laser-derived tree height estimates by means of photogrammetric techniques.Techniques based on laser point clouds and digital terrestrial images were demonstrated for the calibration of tree-height estimation. Individual tree heights can be roughly estimated from laser scanning data by using the approximated ground level and the highest hit of the treetop. However, laser-derived measurements often underestimate tree heights. This underestimation can arise from various error sources. Digital terr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 8 publications
(9 reference statements)
1
14
0
1
Order By: Relevance
“…Hence, the limiting factor of the image-based point clouds is the vertical penetration, which is provided by ALS. Thus the idea of combining photogrammetric image-based DSM with pre-existing historical ALS DTM could be a promising solution for the generation of CHM (Rönnholm et al 2004, St-Onge et al 2004, Jan 2005, Vé-ga & St-Onge 2008, Bohlin et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the limiting factor of the image-based point clouds is the vertical penetration, which is provided by ALS. Thus the idea of combining photogrammetric image-based DSM with pre-existing historical ALS DTM could be a promising solution for the generation of CHM (Rönnholm et al 2004, St-Onge et al 2004, Jan 2005, Vé-ga & St-Onge 2008, Bohlin et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Further, tree height determination from CHM is highly accurate but is prone to underestimation (e.g. Rönnholm et al 2004). If the ground elevation and the uppermost proportion of a crown are not detected, then the tree height is automatically underestimated.…”
Section: Estimation Of Stand and Tree Variables With Individual Tree mentioning
confidence: 99%
“…Rönnholm et al 2004) and usually calibrated using field data. Tree dbh cannot be measured directly from the point cloud and must be predicted.…”
Section: Individual Tree Detectionmentioning
confidence: 99%
“…ALS tends to underestimate tree height (see e.g. Rönnholm et al 2004) due to pulse interactions within the canopy. Rönnholm et al (2004) showed that single tree height was underestimated, on average, by 0.76 m to 1.46 m depending on the tree species.…”
Section: Tree Species Dbh Height and Stem Curvementioning
confidence: 99%
“…Rönnholm et al 2004) due to pulse interactions within the canopy. Rönnholm et al (2004) showed that single tree height was underestimated, on average, by 0.76 m to 1.46 m depending on the tree species. Similar underestimations where found by Maltamo et al (2004), where 46% of the trees were underestimated by > 1 m and 37.4% by < 1 m. Tree DBH can be modelled based on allometric relationship between DBH and height (see e.g.…”
Section: Tree Species Dbh Height and Stem Curvementioning
confidence: 99%